DETERMINANTS OF ZAKAT COMPLIANCE BEHAVIOR IN URBAN MUSLIM ENTREPRENEURS IN MATARAM CITY WEST NUSA TENGGARA - Bonang, Dahlia; Widiastuti, Tika; Yuliatul Hijriah, Hanifiyah; Ismail, Shafinar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2023)
This study aims to assess determinants of small and medium enterprises (SMEs) owners’ compliance behavior in paying zakat (alms). In addition, the sample population comprised 176 SMEs owners in Mataram City who served as participants. Data were collected through online survey instruments using the purposive sampling method. The testing technique and data analysis were carried out using Structural Equation Modeling (SEM). The results showed that zakat literacy, Islamic egalitarianism, and moral norms influenced intention of SMEs owners to pay zakat, while intention affected compliance behavior. This study was essential for zakat institutions to develop new strategies to facilitate compliance behavior, considering the great potential in Indonesia. In addition, the fair and equitable distribution of zakat funds to asnaf (noun group of people worthy of receiving Muslim tithe) was expected to encourage SMEs owners to fulfill their obligation through zakat institutions by increasing the level of trust.